COMMUNITY SERVICE ACTIVITIES FOR ACTUALIZATION OF INVENTORY MANAGEMENT IN SMALL MEDIUM ENTERPRISES - Achmad Yanu Alif Fianto (Universitas Airlangga, 2022)
Small and Medium-sized Entreprises (SMEs) in Surabaya were asked to participate in this project as part of their community service requirement to learn more about the best practices for inventory management. The EOQ and safety stock analysis models are used to do this task. The outcomes of this community service project show that SMEs need to enhance their inventory management. Because of the difficulties in managing inventory in SMEs, this increase is necessary. Inventory management techniques that might enhance small company operating capacities are predicted to be a real benefit of this activity for small businesses.